Synchronised smart phones: The collision of personal privacy and organisational data security - W. Chigona (South African Journal of Business Management, 2012)
The purpose of this study was to explore the organisational and individual motivations for incorporating personally-owned smart phones into the workplace and challenges arising from use; privacy and data security concerns of involved parties in the organisation. This study uses exploratory case study method and investigates privacy and security regarding personally-owned smart-phone usage in workplace. The study found that convenience, ease of use and access to emails were motives behind employees' use of personal smart phones in the workplace. Further, employees have higher privacy expectation. Sample for this study was small to provide statistically meaningful results, Further research is needed to cover a larger case study spanning multiple organisations in other sectors. Mobile devices are creating challenges to organisational data security and employees' right to information privacy. This study suggests that organisations need to reconsider data security and employees' privacy policies to address possible conflict between data security and employees' privacy.
Keywords: 650